2013
DOI: 10.1016/j.febslet.2013.05.020
|View full text |Cite
|
Sign up to set email alerts
|

The cell stress machinery and retinal degeneration

Abstract: a b s t r a c tRetinal degenerations are a group of clinically and genetically heterogeneous disorders characterised by progressive loss of vision due to neurodegeneration. The retina is a highly specialised tissue with a unique architecture and maintaining homeostasis in all the different retinal cell types is crucial for healthy vision. The retina can be exposed to a variety of environmental insults and stress, including light-induced damage, oxidative stress and inherited mutations that can lead to protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
121
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(128 citation statements)
references
References 122 publications
1
121
0
2
Order By: Relevance
“…Therefore, the 9-cis-retinal, which stabilizes P23H opsin, could be needed to treat P23H adRP. Other than supplemental chromophore analogs, new pharmacological chaperones are needed to test whether alleviating UPR (4,63,64) and/or proteasome overload (65) can rescue P23H adRP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the 9-cis-retinal, which stabilizes P23H opsin, could be needed to treat P23H adRP. Other than supplemental chromophore analogs, new pharmacological chaperones are needed to test whether alleviating UPR (4,63,64) and/or proteasome overload (65) can rescue P23H adRP.…”
Section: Discussionmentioning
confidence: 99%
“…2 is a progressive retinal degenerative disease caused by heterogeneous genetic defects that affect more than a million people worldwide (1)(2)(3)(4). The disease is characterized by night blindness and progressive loss of peripheral vision due to rod photoreceptor cell death.…”
Section: Retinitis Pigmentosa (Rp)mentioning
confidence: 99%
“…Further, the Met-450 variant of RPE65 expressed in C57/B6 mice is less active and slows the kinetics of rhodopsin regeneration by 4-fold when compared with the Leu-450 variant expressed by BALB/c mice (22). Thus the difference in the levels of R* generated by the same light exposure to BALB/c and C57 mice can be Ն400-fold, making the albino BALB/c mice an ideal light damage model to isolate the toxic effect of excessive R*, which generates reactive oxygen species and cause oxidative stress (2,24).…”
mentioning
confidence: 99%
“…We showed that prolonged G-protein signaling caused by the lack of ARR1 led to a rapid induction of the PERK arm of the unfolded protein response (UPR) 2 followed by a coordinated increase in global protein ubiquitination and degradation of PDE6 and guanylyl cyclase activating protein 2 (GCAP2). These changes were prevented when G-protein signaling was abolished in the GNAT1 Ϫ/Ϫ background.…”
mentioning
confidence: 99%
“…Degeneration occurs in several chronic retinopathies including glaucoma, DR, age-related macular degeneration, and retinitis pigmentosa [27,28]. However, there is currently no cure for degenerative retinal diseases.…”
Section: Epo Helps Protect the Retina From Degenerationmentioning
confidence: 99%